Answer:
![\huge\boxed{y=\dfrac{2}{3}x-\dfrac{4\sqrt{13}}{3}\ \vee\ y=\dfrac{2}{3}x+\dfrac{4\sqrt{13}}{3}}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7By%3D%5Cdfrac%7B2%7D%7B3%7Dx-%5Cdfrac%7B4%5Csqrt%7B13%7D%7D%7B3%7D%5C%20%5Cvee%5C%20y%3D%5Cdfrac%7B2%7D%7B3%7Dx%2B%5Cdfrac%7B4%5Csqrt%7B13%7D%7D%7B3%7D%7D)
Step-by-step explanation:
The equation of a line:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
We have
![m=\dfrac{2}{3}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7B2%7D%7B3%7D)
substitute:
![y=\dfrac{2}{3}x+b](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B2%7D%7B3%7Dx%2Bb)
The formula of a distance between a point and a line:
General form of a line:
![Ax+By+C=0](https://tex.z-dn.net/?f=Ax%2BBy%2BC%3D0)
Point:
![(x_0,\ y_0)](https://tex.z-dn.net/?f=%28x_0%2C%5C%20y_0%29)
Distance:
![d=\dfrac{|Ax_0+By_0+C|}{\sqrt{A^2+b^2}}](https://tex.z-dn.net/?f=d%3D%5Cdfrac%7B%7CAx_0%2BBy_0%2BC%7C%7D%7B%5Csqrt%7BA%5E2%2Bb%5E2%7D%7D)
Convert the equation:
|<em>subtract
from both sides</em>
|<em>multiply both sides by 3</em>
![2x-3y+3b=0\to A=2,\ B=-3,\ C=3b](https://tex.z-dn.net/?f=2x-3y%2B3b%3D0%5Cto%20A%3D2%2C%5C%20B%3D-3%2C%5C%20C%3D3b)
Coordinates of the point:
![(0,\ 0)\to x_0=0,\ y_0=0](https://tex.z-dn.net/?f=%280%2C%5C%200%29%5Cto%20x_0%3D0%2C%5C%20y_0%3D0)
substitute:
![d=4](https://tex.z-dn.net/?f=d%3D4)
![4=\dfrac{|2\cdot0+(-3)\cdot0+3b|}{\sqrt{2^2+(-3)^2}}\\\\4=\dfrac{|3b|}{\sqrt{4+9}}](https://tex.z-dn.net/?f=4%3D%5Cdfrac%7B%7C2%5Ccdot0%2B%28-3%29%5Ccdot0%2B3b%7C%7D%7B%5Csqrt%7B2%5E2%2B%28-3%29%5E2%7D%7D%5C%5C%5C%5C4%3D%5Cdfrac%7B%7C3b%7C%7D%7B%5Csqrt%7B4%2B9%7D%7D)
|<em>multiply both sides by
</em>
|<em>divide both sides by 3</em>
![b=-\dfrac{4\sqrt{13}}{3}\ \vee\ b=\dfrac{4\sqrt{13}}{3}](https://tex.z-dn.net/?f=b%3D-%5Cdfrac%7B4%5Csqrt%7B13%7D%7D%7B3%7D%5C%20%5Cvee%5C%20b%3D%5Cdfrac%7B4%5Csqrt%7B13%7D%7D%7B3%7D)
Finally:
![y=\dfrac{2}{3}x-\dfrac{4\sqrt{13}}{3}\ \vee\ y=\dfrac{4\sqrt{13}}{3}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B2%7D%7B3%7Dx-%5Cdfrac%7B4%5Csqrt%7B13%7D%7D%7B3%7D%5C%20%5Cvee%5C%20y%3D%5Cdfrac%7B4%5Csqrt%7B13%7D%7D%7B3%7D)
Answer:
-33 or 33
Step-by-step explanation:
The seventh term of an AP is written as:
![a + 6d](https://tex.z-dn.net/?f=a%20%2B%206d)
The eleventh term of an AP is written as:
![a + 10d](https://tex.z-dn.net/?f=a%20%2B%2010d)
If the 7th term is 11 times the 11th term, then;
![a + 6d = 11(a + 10d)](https://tex.z-dn.net/?f=a%20%2B%206d%20%3D%2011%28a%20%2B%2010d%29)
Expand to get:
![a + 6d = 11a + 110d](https://tex.z-dn.net/?f=a%20%2B%206d%20%3D%2011a%20%2B%20110d)
![11a - a = 6d - 110d](https://tex.z-dn.net/?f=11a%20-%20a%20%3D%206d%20-%20110d)
![10a = - 104d](https://tex.z-dn.net/?f=10a%20%3D%20%20-%20104d)
![\frac{a}{d} = - \frac{104}{10}](https://tex.z-dn.net/?f=%20%5Cfrac%7Ba%7D%7Bd%7D%20%20%3D%20-%20%20%20%5Cfrac%7B104%7D%7B10%7D%20)
![\frac{a}{d} = - \frac{52}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7Ba%7D%7Bd%7D%20%20%3D%20-%20%20%20%5Cfrac%7B52%7D%7B5%7D%20)
We must have a=-52 and d=5
Or
a=52 and d=-5
For the first case, the 18th term is :
![- 52 + 5 \times 17 = 33](https://tex.z-dn.net/?f=%20-%2052%20%2B%205%20%5Ctimes%2017%20%3D%2033)
For the second case,
![52 - 5 \times17 = - 33](https://tex.z-dn.net/?f=52%20-%205%20%5Ctimes17%20%3D%20%20-%2033)
-4.2, -3.5,-2.1,-1.5,-1,-0.5,0.5,2,3.5,4.8
Answer:
-37
Step-by-step explanation:
-16+-11=-27
-20+10=-10
-27+-10=-37
Answer:
2
Step-by-step explanation:
because y-5x=3 its very simple math.